Smart Mangrove Monitoring for Resilience and Blue Carbon Governance - Kano Mohamad, Abdurahman; Rustam Anwar; Romi Djafar (LPPM Politeknik Aceh Selatan, 2026)
Mangrove ecosystems provide essential coastal protection, nursery habitat for fisheries, and blue-carbon services; however, many Indonesian coastal areas continue to experience degradation due to land conversion, pollution, and limited monitoring capacity. This article develops a technology-oriented, marine–fisheries governance approach for mangrove rehabilitation by integrating multi-source observation and decision support. The proposed framework combines multi-temporal satellite analysis (e.g., NDVI/NDWI and mangrove-specific vegetation indices), UAV shoreline mapping, and low-power Internet of Things (IoT) sensing to capture both spatial and in situ dynamics of habitat quality. IoT nodes are configured to continuously record salinity, temperature, turbidity, dissolved oxygen, and water level as operational indicators for fisheries-relevant ecosystem conditions, while remote sensing quantifies canopy cover recovery, fragmentation, and coastline change. A data pipeline is designed for near-real-time ingestion, quality control, and anomaly detection to enable early warnings and support evidence-based enforcement. To translate measurements into management actions, the study introduces measurable performance indicators aligned with rehabilitation targets, including seedling survival, canopy recovery rate, shoreline stabilization, and compliance with water-quality thresholds, complemented by community participation and institutional coordination metrics. Scenario analysis demonstrates that the integrated approach improves prioritization of restoration zones, reduces uncertainty compared with single-source assessments, and strengthens monitoring, reporting, and verification (MRV) for blue-carbon initiatives. The framework offers a scalable model for adaptive coastal management that connects ecological monitoring, fisheries sustainability, and governance accountability.